2020
DOI: 10.1128/mbio.00136-20
|View full text |Cite
|
Sign up to set email alerts
|

Barrier-to-Autointegration Factor 1 Protects against a Basal cGAS-STING Response

Abstract: Although the pathogen recognition receptor pathways that activate cell-intrinsic antiviral responses are well delineated, less is known about how the host regulates this response to prevent sustained signaling and possible immune-mediated damage. Using a genome-wide CRISPR-Cas9 screening approach to identify host factors that modulate interferon-stimulated gene (ISG) expression, we identified the DNA binding protein Barrier-to-autointegration factor 1 (Banf1), a previously described inhibitor of retrovirus int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…Linker histones are not the only proteins restricting accessibility of cGAS to nuclear DNA, as the barrier‐to‐autointegration factor 1 (BAF1) can also dynamically outcompete cGAS for DNA binding upon acute loss of nuclear envelope integrity (Guey et al , 2020; Ma et al , 2020) (Fig 5D). BAF1 is a small (10 kDa) chromatin‐bound protein essential for mitosis, nuclear assembly, and the DNA damage response (Haraguchi et al , 2001; Margalit et al , 2005; Haraguchi et al , 2008; Jamin & Wiebe, 2015).…”
Section: A Cytosolic Dna Sensor In the Nucleusmentioning
confidence: 99%
“…Linker histones are not the only proteins restricting accessibility of cGAS to nuclear DNA, as the barrier‐to‐autointegration factor 1 (BAF1) can also dynamically outcompete cGAS for DNA binding upon acute loss of nuclear envelope integrity (Guey et al , 2020; Ma et al , 2020) (Fig 5D). BAF1 is a small (10 kDa) chromatin‐bound protein essential for mitosis, nuclear assembly, and the DNA damage response (Haraguchi et al , 2001; Margalit et al , 2005; Haraguchi et al , 2008; Jamin & Wiebe, 2015).…”
Section: A Cytosolic Dna Sensor In the Nucleusmentioning
confidence: 99%
“…It was first identified as a host protein that captures viral DNA ( 1 , 9–11 ). It binds genomic self-DNA upon loss of nuclear membrane integrity, thus outcompeting cGAS and preventing aberrant immune response ( 12 , 13 ). However, BAF was also described as playing several essential roles during the cell cycle of metazoan cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although BAF is expected to function as a defense against viral infection 23,57,58 , it unexpectedly assists in the integration of the human immunodeficiency virus (HIV) genome into the host genome 15,16 . In addition, a recent report showed that BAF protects against the cGAS-STING response to prevent innate immune activation 59,60 . Collectively, these data suggest that BAF can suppress the innate immune response and act to safely carry the cytosolic DNA to the next cell cycle stages by wrapping it in the NE-like membrane.…”
Section: Discussionmentioning
confidence: 99%